Network analysis of the association between social anxiety and problematic smartphone use in college students - Xing, Wanying; Wang, Xianyang; Feng, Tingwei; Xie, Jiaxin; Liu, Chang; Wang, Xiuchao; Wang, Hui; Ren, Lei; Liu, Xufeng (Frontiers in Psychiatry, 2025)
BackgroundSocial anxiety (SA) and problematic smartphone use (PSU) have become increasingly common among college students in recent decades, with research indicating a mutual increase in risk. This study aim to deepen the understanding of how SA and PSU are interconnected at the symptom-level within this demographic using network analysis.MethodsWe recruited 1,197 college students from four institutions in Shaanxi Province, China. Symptoms of SA and PSU were assessed through self-report questionnaires. A regularized Gaussian graphical model was used to estimate the relationships between these symptoms. We calculated Bridge Expected Influence (BEI) to identify key symptoms contributing to their co-occurrence. Additionally, a network comparison test was conducted to examine potential gender differences in the BEI values of the SA-PSU network.ResultsDistinct relationships were observed between SA and PSU symptoms. Notably, the connections between ‘Get embarrassed very easily’ (SA3) and ‘shyness in new situations’ (PSU1), as well as between SA3 and ‘Escape or relieve negative moods’ (PSU8), showed the strongest inter-construct connections. SA3 and PSU8 were identified as the key symptoms contributing to the co-occurrence, with the highest BEI. Network comparison tests between males and females revealed no significant differences in global expected influence, between-community edges weights, and BEI.ConclusionThe key bridging symptoms this study identified supports the existing theories about the co-occurrence of SA and PSU, and contributes to understanding the underlying mechanisms. Our findings suggest that interventions targeting negative emotions in daily interactions could be effective in reducing PSU.